Potensi Limbah Padat Kelapa Sawit sebagai Bahan Bakar Pembangkit Listrik Tenaga Uap pada Pabrik Kelapa Sawit - Erivianto, Dino; Dani, Ahmad (Neolectura, 2024)
This research aims to analyze the potential electric energy contained in the by-products and processed waste of palm oil. Biomass derived from palm oil by-products can serve as an alternative source of energy, with potential calorific value to generate electricity from boilers or as renewable energy. While solid waste from palm oil by-products is commonly utilized as boiler fuel and fertilizer, it holds promise as a renewable energy source in its entirety. The research process includes problem identification, formulation, determination of research objectives, literature review, field surveys, primary data collection through observation and interviews, data analysis, and presentation of research results. Field observations from several visited palm oil mills reveal that solid waste by-products typically consist of 5-7% shell, 11-14% fiber, and 20-22% Empty Fruit Bunches (EFB) per ton of processed Fresh Fruit Bunches (FFB). Considering the maximum electricity requirement for processing 30 tons/hour and the potential electrical energy contained in each waste type, utilizing fiber waste alone as boiler fuel is sufficient, offering a potential electrical energy of 542.1 kW. Any excess electrical power generated (580 kW) by the boiler can be sourced from shell waste, enabling surplus electricity to be sold to external parties. With the surplus electrical power estimated at 130 – 70 kW/hour, operating for 20 hours per day yields a surplus of 1.4 – 2.6 MW/day from processing. The calorific value of solid palm oil waste is notably affected by its moisture content. Proper management of fiber waste utilization can effectively fulfill the energy needs of palm oil mills. Additionally, there is potential to sell approximately 648 – 686 kW of electrical energy externally, derived from shell waste and EFB.